Improvement of Raman enhancement factor due to the use of silver nanoparticles coated obliquely aligned silicon nanowire arrays in SERS measurements. (9th March 2015) - Ngan, Luong Truc Quynh; Cao, Dao Tran; Anh, Cao Tuan; Vu, Le Van
In this paper, we present the use of silver nanoparticles coated silicon nanowire (SiNW) arrays in surface–enhanced Raman scattering (SERS) measurements with emphasis on the use of obliquely instead of vertically aligned SiNW arrays. The obliquely aligned SiNW arrays were fabricated on Si(111) substrate, and the SiNWs were coated with silver nanoparticles with sizes in the 20–40 nm range. The results showed that with the use of obliquely instead of vertically aligned SiNW arrays, the Raman enhancement factor (REF) is increased by more than one order of magnitude and can reach 10 14 when malachite green is used as test sample. The mechanism causing the improvement of the REF is also discussed.